2008
DOI: 10.1161/circheartfailure.108.766402
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Glucagon-Like Peptide-1 Infusion Sustains Left Ventricular Systolic Function and Prolongs Survival in the Spontaneously Hypertensive, Heart Failure–Prone Rat

Abstract: Background-Glucagon-like peptide-1 (GLP-1) treatment leads to short-term improvements in myocardial function in ischemic and nonischemic cardiomyopathy. It is unknown whether GLP-1 improves survival when administered over a longer time period. Spontaneously hypertensive, heart failure-prone (SHHF) rats progress to advanced heart failure and death over a 15-month period. The authors sought to determine whether a continuous infusion of GLP-1 would reduce mortality in this model. Methods and Results-At 9 months o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
104
0
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(115 citation statements)
references
References 48 publications
5
104
0
6
Order By: Relevance
“…Up to now, seven DPP-4 inhibitors are usable in Japan, including sitagliptin, vildagliptin, alogliptin, linagliptin, anagliptin, teneligliptin, and saxagliptin [93][94][95] . The elevated intrinsic plasma level of GLP-1 is considered to show protective outcomes on the CV system [96] . Ojima et al [97] showed that GLP-1 receptor agonist would inhibit ADMA development in the kidney of streptozotocin-induced DM rats.…”
Section: Adma and Incretin-based Drugsmentioning
confidence: 99%
“…Up to now, seven DPP-4 inhibitors are usable in Japan, including sitagliptin, vildagliptin, alogliptin, linagliptin, anagliptin, teneligliptin, and saxagliptin [93][94][95] . The elevated intrinsic plasma level of GLP-1 is considered to show protective outcomes on the CV system [96] . Ojima et al [97] showed that GLP-1 receptor agonist would inhibit ADMA development in the kidney of streptozotocin-induced DM rats.…”
Section: Adma and Incretin-based Drugsmentioning
confidence: 99%
“…Also, GLP-1 has been reported to improve left ventricular function and remodeling and prolong survival in rats with chronic heart failure (28). Specifically, GLP-1 increases myocardial insulin activity and glucose uptake (36,38,50) and activates kinases of the so-called reperfusion injury salvage kinase pathway (RISK pathway) (7,19). Of interest, GLP-1 has been described as an antiapopotic factor in different cell types, including cholangyocytes (29), neuronal cells (23,27,39), and pancreatic ␤-cells (6,12,26,45).…”
mentioning
confidence: 99%
“…61 A 3-month course of continuous GLP-1 agonist infusion in spontaneously hypertensive heart failure-prone obese rats was associated with prolonged survival, preserved LV function, enhanced myocardial glucose uptake, and reduced apoptosis. 62 GLP-1 infusion in dogs with pacing-induced cardiomyopathy resulted in significant increases in stroke volume and cardiac output. 63 …”
Section: Animal Modelsmentioning
confidence: 95%